Strategy Formulation Analysis With Company Implementation in Dealing With The Covid-19 Pandemi Situation - Rizalullah Mudzakkir; Muhammad Azhar Tamim; Dian Hakip Nurdiansyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The Covid-19 virus which has swept the world and become a global pademic has changed the world order. The reduced social economic activities of the community to reduce social interaction that can accelerate the spread of the virus, resulting in a decline in the performance of economic sectors. Many industries experience a decline in revenue and can result in further cessation of company operations. The Covid-19 pandemic to date has not been able to predict how long it will end which causes uncertainty about the future. In order for a company to continue to exist and grow sustainably, it is very important to formulate a future strategy that is full of uncertainty. Pizza Hut is one of the American restaurants and international franchises founded in 1958 in Wichita, Kansas by Dan and Frank Carney. The company is known for its Italian-American food, including pizza and pasta as well as side dishes and desserts. This research aims to implement marketing strategies to achieve excellence in the midst of this pandemic. The results showed that the marketing strategy used by Pizza Hut can increase sales volume by staying, even if selling on the side of the road. As well as the presence of information technology provides many benefits for Pizza HUT, such as being able to alleviate complex business activities as well as produce information that is trustworthy, relevant on time, complete, understandable and tested in the framework of planning, controlling and making management decisions. The results showed that the marketing strategy used by Pizza Hut can increase sales volume by staying, even if selling on the side of the road. As well as the presence of information technology provides many benefits for Pizza HUT, such as being able to alleviate complex business activities as well as produce information that is trustworthy, relevant on time, complete, understandable and tested in the framework of planning, controlling and making management decisions. The results showed that the marketing strategy used by Pizza Hut can increase sales volume by staying, even if selling on the side of the road. As well as the presence of information technology provides many benefits for Pizza HUT, such as being able to alleviate complex business activities as well as produce information that is trustworthy, relevant on time, complete, understandable and tested in the framework of planning, controlling and making management decisions. Keywords: Covid-19, Management Strategy, and Strategy Formulation